Clinical effect and follow-up of laparoscopic radical proximal gastrectomy for upper gastric carcinoma - Meng, Wei; Ya-di, Huang; Wei-bo, Cao; Ru-dong, Zhao; Ze-wei, Cheng; Ou Yang, Jun; Ze-peng, Yan; Chuan-qi, Chen; Yi-ze, Liang; Dan-ping, Sun; Wen-bin, Yu (Frontiers in Oncology, 2023)
Objective: To evaluate the safety and clinical effect of tubular esophagogastric anastomosis in laparoscopic radical proximal gastrectomy. Methods: Retrospective analysis was performed on 191 patients who underwent laparoscopic radical proximal gastrectomy in the Department of Gastrointestinal Surgery, Qilu Hospital of Shandong University from January 2017 to October 2020. Patients were divided into tubular esophagogastric anastomosis group (TG group) and traditional esophagogastric anastomosis group(EG group) according to the digestive tract reconstruction, and the intraoperative conditions, perioperative recovery and postoperative follow-up were compared. In addition, 191 patients were divided into indocyanine green group and non- indocyanine green group according to whether indocyanine green tracer technology was used during the operation, and the intraoperative situation and perioperative recovery of the two groups were compared and analyzed after propensity score matching. Results: All patients completed the operation successfully. Compared with the EG group, the TG group had less volume of gastric tube drainage, shorter gastric tube drainage time and proton pump inhibitors application time, and the reuse rate of proton pump inhibitors of the TG group was lower. According to the anastomotic width and dysphagia score, the incidence of anastomotic stenosis was higher in TG group than that in EG group at 3rd month after surgery. While the incidence of reflux esophagitis and postoperative quality of life score in TG group were lower than those in EG group at 1st and 2nd year after surgery. In the indocyanine green analysis, the total operation time and lymph node dissection time in the indocyanine green group was significantly less than that in the non-indocyanine green group. The intraoperative blood loss of the indocyanine green group was significantly less than that of the non-indocyanine green group, and the number of postoperative lymph nodes obtained was more than that of the non-indocyanine green group. Conclusion: Laparoscopic radical proximal gastrectomy for upper gastric cancer is safe and effective. Tubular esophagogastric anastomosis has more advantages in restoring postoperative gastrointestinal function and reducing reflux, but it has a higher incidence of postoperative anastomotic stenosis. The application of indocyanine green tracer technique in laparoscopic radical proximal gastrectomy has positive significance.